2023
DOI: 10.1002/jad.12198
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional relationship between bullying victimization and functions of aggression in adolescents: The mediating effect of teacher justice

Abstract: Introduction Bullying victimization and aggression are frequent phenomena among adolescents and have been linked to various mental health problems. Although the correlation between bullying victimization and aggression is well‐documented, the direction between the two has been debated. Moreover, the underlying mechanism through which victimization influences aggression or vice versa has gained little attention. The current study used data across two‐time points to address this gap and explore the reciprocal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…However, bullying itself is a cycle, in the sense that the current perpetrator is most likely the victim of a previous perpetrator of bullying. 4 Generally, adolescents who have economic and physical disadvantages (disabilities) easily become victims of bullying by their friends. 5 There are various forms of bullying, it can take the form of teasing, insults or beatings.…”
Section: Methodsmentioning
confidence: 99%
“…However, bullying itself is a cycle, in the sense that the current perpetrator is most likely the victim of a previous perpetrator of bullying. 4 Generally, adolescents who have economic and physical disadvantages (disabilities) easily become victims of bullying by their friends. 5 There are various forms of bullying, it can take the form of teasing, insults or beatings.…”
Section: Methodsmentioning
confidence: 99%
“…Little research, however, has explicitly focused on the influence of teacher unfairness for reactive and proactive aggression separately. To the best of our knowledge, only one study conducted with a large sample of Chinese adolescents (Ren et al, 2023) has provided preliminary results on the association between perceived teacher unfairness and reactive and proactive aggression. Even though it was not the main aim of that study, the authors found positive bivariate correlations between teacher unfairness and both reactive and proactive aggression, both concurrently and longitudinally after 6 months.…”
Section: Perceived Teacher Unfairness and Peer Aggressionmentioning
confidence: 99%